Influence of the extraction method on the yield and quality of bacaba palm oil from southwestern Amazonia - V.S. Álvares; J.M.L. Souza; E.J.L. Ferreira; V.T. Maciel; A.L.S. Madruga (Grasas y Aceites)
This study evaluated the extraction, yield and physicochemical quality of the oil extracted from the fruit mesocarp of the bacaba palm using the artisanal, mechanical pressing and artisanal reheating methods. The oil was stored at 26 °C and 81% RH for 365 days and analyzed for free fatty acids, peroxide value and refractive index. Artisanal extraction resulted in low oil yield and quality. Cold pressing was the most advantageous method, resulting in a higher yield per harvest and an oil with lower acidity. Prolonged storage, even in amber packaging, did not maintain the quality of the oil after 180 days. The acidity of the oil was high from all three extraction methods, indicating its unsuitability for food use. This, however, may have been the result of improper handling of the fruits during the experiment.